Partisipasi Pemilih Perempuan pada Pemilihan Kepala Daerah Serentak di Kelurahan Sumber Harta Kabupaten Musi Rawas Tahun 2020 - Murahman, Mardi; Aprudi, Syafri (Jurnal Publisitas, 2023)
The aim of this study was to she the female voter’s participation in giving their vote of village Head Election of 2020 in Sumber Harta sub-district. The variable’s aspect of this study included psychology, Motive contribution and the accountability from the female voters. This is qualitative study through primary data obtained from observation and interview while scondary data obtained from decomentation related whit the study. Analizyng data technique was in the from of data reduction, data display and drawing conclusion. The result of this study showed that the female voter’s participation in giving their vote of Village Head Election of 2020 in Sumber Harta sub-district was good, it was increased year by year it could be see from their awareness, their emphaty to the election to the election in rejecting money politic.